ASSESSMENT OF POLLEN VIABILITY AND FLORAL BIOLOGY IN SWEET ORANGE (CITRUS SINENSIS OBSECK) CULTIVARS UNDER SUBTROPICAL CONDITIONS OF PUNJAB - A. K. BASWAL; H. S. RATTANPAL; GURUPKAR SINGH SIDHU (The Bioscan, 2015)
Assessment of pollen viability is an essential tool to check the level of sterility as it limits sexual hybridization. The percentage of viable pollen of 20 sweet orange cultivars was evaluated. The viability percentage values ranged from 5.0% for ‘New Hall Navel’ orange to 80.0% for ‘Mosambi’ sweet orange. The ‘Mosambi’ sweet orange cultivar showed the highest percentage of viable pollen, while viable pollen were absent in navel oranges. The cultivars ‘New Hall Navel’, ‘Cara Cara Navel’ and ‘Washington Navel’, sweet orange cultivars, showed the lowest percentage of viable pollen (5.00%, 5.50% and 5.75% respectively). Among flower characters, cultivar Campbell Valencia recorded with highest flower diameter and flower length (41.21 mm and 29.67 mm, respectively) while petal length and petal width was recorded maximum in Campbell Valencia and Cutter Valencia (23.65 mm and 9.34 mm, respectively).